THEORETICAL BASICS OF THE HR-ENGINEERING SYSTEM AT A MODERN ENTERPRISE - VOLIANSKA-SAVCHUK, Lesia; DURACH, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article explores the principles of determining the HR engineering development strategy as a factor in ensuring the high competitiveness of the company's personnel. The main prerequisites for the emergence of the concept of the competitiveness of the company's personnel are considered. The essence of the concept of "staff competitiveness" is determined, which includes the set of competitive advantages of all employees of the organization. An overview analysis of the factors affecting the competitiveness of the foreign worker, which are directly related to the characteristics of the labor market, was carried out. The main element of achieving the long-term competitive position of the enterprise today is the same strategic HR engineering. An overview analysis of the main principles of HR engineering was carried out. The task that solves the implementation of the HR-engineering system at a modern enterprise has been created. The structure of HR processes in the context of the application of the engineering approach is considered. The implementation of changes in the personnel management process at the enterprise using engineering technologies is characterized. The positive consequences of the practical application of the business process engineering method at enterprises have been formed.
Keywords: HR engineering; personnel competitiveness; HR technologies; HR strategy; personnel management